Esophageal hiatus hernias: Esophageal analysis therapeutic indications. 64 observations - Suiffet, Walter; Ituño, Carlos; Estapé, Gonzalo (Cirugía del Uruguay, 1972)
The characteristics of herniation of the esophageal foramen of the diaphragm are discussed. Stress is laid on· the importance of esophagitis due to backflow regurgitation in the. ascending type. The author Iists the elements considered necessary in deciding whether surgery jr necessary, since this therapy does not apply to all cases. This is followed by an analysis of 64 cases treated by surgery. The decision for applying this therapy was based on the following elements: symptomatic manifestations, anemia, backflow regurgitation, esophagitis, complications or associated pathology (bi!iary or _gratoduodenal). Cases not requiring surgery are analyzed. ( symptornatic, without backflow isolated radiological findings) , vointing out however, that they should be carefully observed, because surgery rnay eventually become necessary in the course of their evolution. The conclusion arrived at is that backflow and esophagitis should be stopped befare they cause serious morphological alterations which are difficult to treat. A high percentage of herniations of the esophageal foramen require surgery and this therapy is more widely applied as a result of better knowledge of pathology and surgical tactics.